(untitled) (Journal of the College of Education for Women, 2010)
Hedging is a linguistic avoidance of full commitment or precision. It is the use of a vague language. The main objectives of this study are to: (1) identify and classify the linguistic devices which act as hedges; (2) to examine the semantic functions of these devices. This paper makes use of word class as well as clausal constructions to represent the forms of hedges in relation to certain grammatical categories, namely: adverbials, epistemic verbs, modal verbs, cognitive verbs, hypothetical constructions, anticipatory it-clause, and anticipatory constructions. The text analysed is the first presidential debate between Senator Barak Obama and Senator John McCain on the campus of the University of Mississippi, during the presidential election campaign of the Republican and the Democrat parties in America.The results show that politicians use hedges to mild their language in process to, so that not to be proved wrong later. This justification is that the claims they had already made were only an approximation to the statements.